The Implementation of Knowledge Management on Fraud Prevention of PT Bahagia Idkho Mandiri - Farkhan, Herdimas Muhammad; Indahdewi, Lauditta (Devotion : Journal of Research and Community Service, 2023)
Fraudulent behaviors offer a serious danger to companies since they can result in considerable financial losses, harm the company's reputation, and a decline in stakeholder confidence. This research examines the effects of fraud on PT BIM and how knowledge management can serve as a preventative measure against fraudulent activities. It also seeks to assess the potential impact of knowledge management in reducing fraud risks and boosting the company's fraud prevention system. This research uses qualitative methods to explore fraud inside PT BIM, interviewing personnel and revealing potential benefits of knowledge management implementation in fraud prevention. Knowledge management can improve the company's capacity to detect and prevent fraud by cultivating an awareness and vigilance culture among employees. It can help in the establishment and implementation of strong internal controls and policies that act as effective fraud deterrents. It can also aid in the identification of developing fraud trends and patterns, allowing companies to adjust their fraud protection methods accordingly. PT BIM can use knowledge management frameworks such as the SECI Model to improve internal controls, increase staff knowledge, and respond quickly to new fraud concerns. This allows for the rapid broadcast of information about developing fraud tendencies, new methods of operation, and preventive measures.